Long-term follow-up reveals high incidence of colorectal cancer in Indian patients with inflammatory bowel disease. Issue 5 (August 2017) - Bopanna, Sawan; Kedia, Saurabh; Das, Prasenjit; Dattagupta, S; Sreenivas, V; Mouli, V Pratap; Dhingra, Rajan; Pradhan, Rajesh; Kumar, N Suraj; Yadav, Dawesh P; Makharia, Govind; Ahuja, Vineet
Background: As the magnitude of sporadic colorectal cancer (CRC) in India is low, magnitude of CRC in ulcerative colitis (UC) is also considered low. As a result, screening for CRC in UC although advocated may not be followed everywhere. We report our data of UC-related CRC from a low-incidence area of sporadic CRC. Methods: A total of 1012 patients with left-sided colitis/pancolitis having more than one full-length colonoscopy performed at least a year after the onset of symptoms were included in retrospective analysis of prospectively maintained case records. In addition, 136 patients with duration of disease >10 years underwent surveillance white-light colonoscopy prospectively during the study period. Results: A total of 1012 individuals were finally included (6542 person-years of follow-up, 68.5% males, disease duration: 6.4 ± 6.8 years). Twenty (1.97%) patients developed CRC. Two (10%) patients developed CRC during the first decade, 10/20 (50%) during the second and 8/20 (40%) after the second decade of disease. The cumulative risk of developing CRC was 1.5%, 7.2% and 23.6% in the first, second and third decade, respectively. Of 136 high-risk UC cases, five (3.6%) had CRC on screening colonoscopy. Disease duration and increasing age of onset were associated with higher risk of CRC. Conclusions: Cumulative risk of CRC in Indian UC patients is as high as 23.6% at 30 years. The risk of CRC increases with increasing age of onset and increasing duration of disease. A low risk of sporadic CRC does not confer a low risk of UC-related CRC, and regular screening is warranted.